The Legal Validity of Legal Protection for Holders of Electronic Land Certificates (E-Certificates) in Indonesian Land Law - Rahayu, Rika Rahmania; Sesung, Rusdianto (Journal of Law, Politic and Humanities, 2025)
The digitalization of Indonesia's land administration through electronic land certificates (e-certificates) represents a major innovation toward modern and efficient land governance. E- certificates aim to enhance service efficiency, legal certainty, and the prevention of land disputes. However, questions remain regarding the legal validity and enforceability of e-certificates, particularly due to the lack of explicit provisions in the Basic Agrarian Law (UUPA). This study examines the legal foundation, validity, and legal protection afforded to e-certificate holders, while also identifying potential legal issues arising in its implementation. A normative juridical qualitative method is applied to analyze relevant regulations and legal documents. Findings indicate that while e-certificates are administratively valid under Ministerial Regulation ATR/BPN No. 1 of 2021, substantive legal protection requires regulatory reinforcement and robust digital security systems. Policy recommendations are offered to strengthen public trust and ensure equitable digital-based land governance. Keywords : Legal Validity, Electronic Certificate, Land Affairs